Qualitative drivers of postoperative prophylactic antibiotics use and resistance in Ethiopia - Samantha Steeman; Maia R. Nofal; Ibrahim Heyredin; Hailemichael Asmamaw; Assefa Tesfaye; Alex Zhuang; Natnael Gebeyehu; Sylvia Bereknyei Merrell; Thomas G. Weiser; Tihitena Negussie Mammo (BMC, 2024)
Abstract Background The World Health Organization (WHO) cautions against unnecessary prolongation of postoperative antibiotics to prevent surgical site infections (SSI), however this practice is still common in many countries. This study aims to describe drivers of prolonged postoperative antibiotic prescribing and clinicians' perspectives on antibiotics resistance and stewardship in Ethiopia. Methods We conducted semi-structured interviews of 16 surgeons and nine surgical ward nurses at three academic referral hospitals in Addis Ababa. Audio recordings were transcribed verbatim and coded. Codes were inductively and iteratively derived between two researchers, tested for inter-rater reliability (IRR), and the codebook was consistently applied to all transcripts. Thematic analysis was performed to understand drivers of prolonged prophylactic antibiotic use in surgical patients. Results Interviews revealed factors contributing to postoperative prophylactic antibiotics overprescribing, including inadequate infection prevention and control (IPC) practices, wide variability in local prescribing practices, and distrust in the applicability of WHO guidelines. Antimicrobial resistance was also identified as a major concern by staff. Barriers to improving stewardship included a lack of multidisciplinary teamwork to inform prescribing decisions, while solutions included constructing appropriate context-specific guidelines and improving evidence-based practices through input from local stakeholders, including surgeons, clinical pharmacists, and nurses. Conclusions Study participants perceived that existing evidence and guidelines did not apply in their settings due to high rates of surgical site infections and gaps in perioperative IPC practices (e.g., availability of water for handwashing, sterility breaches). These gaps were a key contributor to prophylactic antibiotic overprescribing, reinforcing the need to strengthen upstream and perioperative surgical antisepsis processes. The findings of this study underscore the importance of engaging multidisciplinary teams in strengthening antimicrobial stewardship efforts, aligning processes to achieve compliance with best practices, and the need for rigorous, contextually appropriate studies from these settings to inform policy.